Current distribution in a rectangular flow channel manufactured by 3‐D printing. Issue 3 (30th August 2016) - Figueredo‐Rodríguez, Horacio A.; McKerracher, Rachel D.; Ponce de León, Carlos; Walsh, Frank C.
Abstract : The characterization and improvement of a rectangular channel electrolyte flow compartment used in an iron‐air flow battery was carried out by using an arrangement of copper electrodes to measure the current density distribution employing the limiting current technique. The present work addresses the hydrodynamics and mass transport distribution in the compartment and their improvement by an improved electrolyte compartment that results in a more uniform current distribution. The current distribution was evaluated as the ratio between the local and the averaged limiting current densities during the reduction of copper ions over a range of mean linear flow velocity across the electrode surface (2–30 cm s −1 ). The initial compartment, showed larger differences between the minimum and maximum currents than the electrolyte compartment that resulted as part of the design process and showed a higher pressure drop at a given mean linear flow velocity. © 2016 American Institute of Chemical Engineers AIChE J, 63: 1144–1151, 2017